Gender and Educational Dimensions of Handicraft Industry in Mwala District, Kenya - Mutinda, Jane; Kiumbuku, Samuel (International Journal of Humanities and Social Science, 2014)
In Kenya, communities have since time immemorial practised indigenous technologies such as woodcarving and basket weaving. The “kiondo” (African Basket) for example, is now an international handicraft while the woodcarvings are exported to all parts of the world as artefacts. In Kenya today, woodcarvings, basketry, Kisii soapstone carvings, jewellery, pottery, gourd decorations, T-shirts and kikois (African shawl), are the major handicrafts. The study was on woodcarving and basket weaving handicrafts among the Kamba community in Wamunyu and Katangi locations of Mwala District in Kenya. It examined the gender and educational dimensions of the two crafts. A total of 100 woodcarvers and 100 basket weavers participated in the survey. These were purposively sampled for the reason that in each location, the target respondents were organised into a major association and groups. In Wamunyu the major association was Wamunyu Cooperative Society whereas in Katangi the basket weavers were organized into groups namely; Yatta South Women Group; Syokisinga Women Group; Assumption Resource Centre; and Katanga women group. Other study respondents included cooperative officials and, programme managers of local Non-Governmental Organisations. Questionnaires, in-depth interview guides, focus group discussions, observation and photography were used in collecting data which revealed certain significant aspects of the handicraft.
Keywords: Gender; Mwala; Handicraft, Woodcarving, Basket weaving